Fluctuation control for many-to-one routing in wireless sensor networks - Jing, Gang (2013)
This paper presents a distributed and adaptive fluctuation control scheme for many-to-one routing (FCM) in wireless sensor networks. Unlike well-known topology control schemes, the primary design objective is to reduce the fluctuation which happens due to overload of sensors in a data collection tree. More specifically, an estimation model of a sensor available capacity based on the number of its neighbors is proposed. In addition, this paper proposes a parent selection mechanism by three-way handshake. With such model and the selection mechanism, it is ensured that the load of a sensor does not exceed its available capacity. Finally, an adaptive maintenance mechanism is proposed to adjust the estimation of a sensor available capacity as the network environment changes. Simulation results demonstrate the effectiveness of the scheme.